Acid-promoted rearrangement of carbonate functionality anchored to the lower rim of a calix[4]arene skeleton: A new class of chiral calix[4]arene and its chiroptical properties - Hesek, D; Inoue, Y; Drew, M; Beer, P; Hembury, G; Ishida, H; Aoki, F (2000)
(equation presented) A unique calix[4]arene lower-rim intramolecular rearrangement, resulting in molecular asymmetry arising from the upper- and lower-rim substitution pattern, produces a new class of inherently chiral calix[4]arenes in a partial cone conformation. This was aided by molecular rigidification arising from π-π and C-H⋯π interactions between bulky lower-rim substituents, with the corresponding circular dichroism spectra exhibiting the most intense bisignate Cotton effects yet observed for calix[4]arenes not bearing a chiral center.